LncRNA DGCR5 suppresses neuronal apoptosis to improve acute spinal cord injury through targeting PRDM5. Issue 16 (18th August 2018) - Zhang, Huafeng; Wang, Wengang; Li, Ning; Li, Peng; Liu, Ming; Pan, Junwei; Wang, Dan; Li, Junwei; Xiong, Yuanyuan; Xia, Lei
ABSTRACT: Spinal cord injury (SCI) usually results in neurological damage. DGCR5 is closely related to neurological disorders, and this study aims to explore its role in neuronal apoptosis in acute SCI. The ASCI model was established in rats, and the Basso, Beattie, and Bresnahan (BBB) scoring was used to assess the neurological function. The expression of RNA and protein was quantified by quantitative real-time PCR (qRT-PCR) and western blotting, respectively. The oxygenglucose deprivation (OGD) was performed upon neurons and apoptosis was evaluated by flow cytometry. The interaction and binding between DGCR5 and PRDM5 was detected with RNA pull-down and RIP assay, respectively. DGCR5 was down-regulated in ASCI model rat and in neurons treated with hypoxia. Over-expression of DGCR5 inhibited neuronal apoptosis. Interaction between DGCR5 negatively regulated PRDM5 protein expression by binding and interacting with it. DGCR5 inhibited neuronal apoptosis through PRDM5. Over-expressed DGCR5 ameliorated ASCI in rat. DGCR5 suppresses neuronal apoptosis through directly binding and negatively regulating PRDM5, and thereby ameliorating ASCI.